THE EFFECTIVENESS OF THE PROBLEM BASED LEARNING MODEL IN IMPROVING LEARNING OUTCOMES OF CLASS VII STUDENTS IN THE SUBJECT OF SOCIAL SCIENCE AT SMP Al FALAH - Parhanudin Nudin; Ismeirita _ (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
Parhanudin, 2023.